Transforming Administrative Justice Insights Indonesian State Dispute Resolution: Transformasi Wawasan Peradilan Administrasi Penyelesaian Sengketa Tata Usaha Negara Indonesia - Ariky, Iqbal Maula; Rato, Dominikus; Setyawan, Fendi (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the role of administrative remedies in resolving state administrative disputes in Indonesia, particularly in light of Supreme Court Regulation No. 6 of 2018. It investigates the legal obligations and procedural mechanisms governing the utilization of administrative remedies, with a focus on disputes involving Civil Servants (ASN). Utilizing a juridical-normative approach, the research underscores the importance of exhausting administrative remedies before resorting to judicial measures, highlighting the potential consequences of failing to do so. Findings indicate that administrative remedies play a crucial role in safeguarding citizens' legal rights, while judicial authorities retain discretion to dismiss cases lacking administrative recourse. The study underscores the need for adherence to procedural requirements and administrative lawfulness, offering insights for legal practitioners, policymakers, and judicial authorities to enhance the administrative justice system in Indonesia. Highlights: Exhausting administrative remedies crucial for procedural fairness in state disputes. Judicial discretion vital; dismissal possible without exhausting administrative remedies. Legal practice and policy must prioritize procedural compliance and enhancement. Keywords: Administrative Remedies, State Administrative Disputes, Legal Obligations, Procedural Mechanisms